Tackling the Issue of Limited Dialogue and Strengthening Collaboration Among Court Actors for Improving the Condition-Setting Process - Phillips, Loveline C. (Criminal justice and behavior, 2025)
The concept of the courtroom workgroup highlights the collaboration among judges, prosecutors, and defense attorneys in the criminal justice system. Traditionally, this workgroup excludes probation officers, presenting a significant gap in information for sentencing and probation condition-setting processes. Our study explores probation officers’ perspectives on their roles within the courtroom workgroup, emphasizing their importance in sentencing and rehabilitation. Using qualitative data analysis from 85 probation staff and the novel application of causal loop diagrams, we reveal how improved communication and integration of probation expertise may foster better collaboration among court actors. Effective communication, respect for probation expertise, and positive relationships foster better collaboration and more balanced and informed decisions. Conversely, poor communication, lack of respect, high turnover rates, and hierarchical power structures hinder dialogue and collaboration. Addressing these issues could lead to more informed decisions, ultimately advancing justice and fairness within the court system.